Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2135/cropsci2014.02.0155
|View full text |Cite
|
Sign up to set email alerts
|

Indaziflam Effect on Bermudagrass (Cynodon dactylon L. Pers.) Shoot Growth and Root Initiation as Influenced by Soil Texture and Organic Matter

Abstract: Indaziflam is an alkylazine herbicide used for preemergence control of annual weeds in warm‐season turfgrass. Growth chamber studies were conducted to determine the effect of indaziflam rate on bermudagrass (Cynodon dactylon L. Pers.) shoot and root initiation as influenced by soil texture and organic matter (OM). Bermudagrass plants propagated from stolons were planted in five different growing media, including pure sand (100% sand), sand (92% sand, 6% clay) with or without OM (2%), and loamy sand (82% sand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
4
19
0
1
Order By: Relevance
“…This small difference could partially explain the absence of phytotoxicity effects in young pecan trees exposed even to an application rate two times greater than the recommended application field rate of indaziflam. Schneider et al (2015) reported increased sorption of indaziflam with increasing organic matter content after evaluating the phytotoxicity of indaziflam on bermudagrass.…”
Section: Resultsmentioning
confidence: 99%
“…This small difference could partially explain the absence of phytotoxicity effects in young pecan trees exposed even to an application rate two times greater than the recommended application field rate of indaziflam. Schneider et al (2015) reported increased sorption of indaziflam with increasing organic matter content after evaluating the phytotoxicity of indaziflam on bermudagrass.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, field experiments evaluating long‐term survival of seedlings established within HPPs are crucial. Soil organic matter content, soil volumetric water content, soil texture, indaziflam application rate, and rooting depth of plants all affect the amount of injury caused by indaziflam to postgerminative establishment of grass species (Gomez de Barreda et al ; Jones et al ; Schneider et al ; Jeffries & Gannon ). The long‐term effects of HPPs have not been studied and it is unknown if they will limit indaziflam injury beyond early seedling growth.…”
Section: Discussionmentioning
confidence: 99%
“…The factors affecting the sorption processes determine the other routes to be taken by the herbicides in the soil. The bioavailability for weed absorption can be altered with the addition of OM in the soil, and there may be a reduction in the risk of phytotoxicity of the herbicide (Szmigielski et al, 2009;Gannon et al, 2014;Schneider et al, 2015). For acidic, polar, and low pK a herbicides, this influence of OM on the behavior of the product in the environment may be lower, since they have low affinity of sorption with the SOM (Stevenson, 1972).…”
Section: Organic Matter Of the Soil In Retention Of Herbicidesmentioning
confidence: 99%